A Critical Analysis of Problems Encountered by Informal Female Cross Border Traders in Zimbabwe - Moyo, Annah (Research and Scientific Innovation Society, 2022)
Due to the failure of the Zimbabwean economy in the past two decades and the subsequent collapse of the formal sector in the country cross border trading has become increasingly popular in the country and likewise the involvement of women in the sector. Remunerations which is earned through informal female cross border trading is not only benefiting their respective households but contribute to the GDP of the country through payment of customs exercise duty, tax on importation of goods, and other government charges and hence women are major contributors to the economy of Zimbabwe. Nonetheless, despite the contributions by women, the challenges and benefits involved with informal cross border traders are based on gender. Unfortunately, there is lack of information on the challenges and stressors faced by females in cross border trading in Zimbabwe. It is against this background that the present study seeks a critical analysis of problems encountered by informal female cross border traders in Zimbabwe and also determining the coping strategies. A qualitative method was adopted in primary data collection and it was achieved through the use of interviews. The snowball sampling method was used to select the females that participated as respondents. The study noted that female cross border traders in Zimbabwe facing serious and deep rooted challenges in the process of conducting their trade from government officials, restriction to access of loans, and health issues emanating from stress and leads to other serious mental health issues like depression, anxiety, tendency of self-harm, and suicide. The study also noted that begging, creating personal savings, and visiting health institutions and employing selfmedication were the most common coping strategies applied by the female cross border traders.